An energy approach to the solution of partial differential equations in computational mechanics via machine learning: Concepts, implementation and applications - Samaniego, E.; Anitescu, C.; Goswami, S.; Nguyen-Thanh, V.M.; Guo, H.; Hamdia, K.; Zhuang, X.; Rabczuk, T. (Computer methods in applied mechanics and engineering, 2020)
Partial Differential Equations (PDEs) are fundamental to model different phenomena in science and engineering mathematically. Solving them is a crucial step towards a precise knowledge of the behavior of natural and engineered systems. In general, in order to solve PDEs that represent real systems to an acceptable degree, analytical methods are usually not enough. One has to resort to discretization methods. For engineering problems, probably the best-known option is the finite element method (FEM). However, powerful alternatives such as mesh-free methods and Isogeometric Analysis (IGA) are also available. The fundamental idea is to approximate the solution of the PDE by means of functions specifically built to have some desirable properties. In this contribution, we explore Deep Neural Networks (DNNs) as an option for approximation. They have shown impressive results in areas such as visual recognition. DNNs are regarded here as function approximation machines. There is great flexibility to define their structure and important advances in the architecture and the efficiency of the algorithms to implement them make DNNs a very interesting alternative to approximate the solution of a PDE. We concentrate on applications that have an interest for Computational Mechanics. Most contributions explore this possibility have adopted a collocation strategy. In this work, we concentrate on mechanical problems and analyze the energetic format of the PDE. The energy of a mechanical system seems to be the natural loss function for a machine learning method to approach a mechanical problem. In order to prove the concepts, we deal with several problems and explore the capabilities of the method for applications in engineering. •Proof of concept for the possibility of approximating the solution of BVPs using concepts and tools coming from deep machine learning.•The energy is the basis for the construction of the loss function.•The approximation space is defined by the architecture of the neural network.•The approach is applied to several engineering problems including linear elasticity, elastodynamics, nonlinear hyperelasticity, plate bending, piezoelectricity and phase field modeling of fracture.